Calculating pressure with elastic geobarometry: a comparison of different elastic solutions with application to a calc-silicate gneiss from the Rhodope Metamorphic Province - Moulas, Evangelos; Kostopoulos, Dimitrios; Podladchikov, Yury; Chatzitheodoridis, Elias; Schenker, Filippo L.; Zingerman, Konstantin M.; Pomonis, Panagiotis; Tajcmanová, Lucie (Lithos, 2020)
Raman elastic geobarometry has increasingly been used complementary to metamorphic phase equilibria to estimate the conditions of recrystallization in metamorphic rocks. The procedure of applying Raman elastic barometry to host-inclusion mineral systems requires several steps that involve various assumptions. One of the most essential assumptions is that the mineral host-inclusion system behaves in an elastic and reversible manner. We discuss the discrepant results obtained by different authors employing different analytical solutions for elasticity and explore the assumptions lying behind each method. Furthermore, we evaluate numerically linear and non-linear elastic solutions and show their discrepancies. Both formulations are tested against recently published experiments on quartz inclusions in garnet (QuiG) at pressures up to 3 GPa, and we find a very good agreement between calculated and experimental pressure values (within 10% relative error). We subsequently apply our new elastic geobarometer to a calc-silicate gneiss from the Rhodope Metamorphic Province (N. Greece). The results of Raman elastic barometry combined with garnet-clinopyroxene geothermometry yield eclogite-facies conditions (~720 ± 40 °C, ~1.5 ± 0.2 GPa). These results are comparable to a high-temperature metamorphic overprint deduced from phase equilibria modeling in surrounding lithologies (730 ± 40 °C, ~1.2 ± 0.1 GPa). Our findings indicate that the estimated pressure from Raman elastic barometry is consistent with a significant viscous relaxation at high temperatures. We conclude that although Raman elastic barometry is a powerful tool for pressure estimation in metamorphic rocks, its pressure estimates do not necessarily correspond to entrapment conditions. Our results are consequential for the estimates of reaction overstepping in high-grade metamorphic rocks.